Asuhan Keperawatan Pada Keluarga Ny. R yang Mengalami Diabetes Mellitus Menggunakan Intervensi Walking Exercise: Studi Kasus - Rasdiyanah Rasdiyanah; Ulfiyah Andi Alifah Nur; Aidah Fitriani; Gandi Purwanto (Nursing Practice Journal, 2025)
The results of a survey in the working area of ​​the Pacellekang Health Center, especially in Tambung Batu Hamlet, showed that cases of diabetes mellitus (DM) were in the second highest position after hypertension, so special attention is needed to prevent an increase in cases of diabetes mellitus and prevent complications. The aim was to analyze nursing care for the family of Mrs. R who had diabetes mellitus with ineffective health management using walking exercise interventions in the working area of ​​the Pacellekang Health Center, Gowa Regency. This study used a case study method with data collection techniques starting from family studies using observation and interview methods. Walking exercise interventions were given to Mrs. R according to the schedule 4 times in 2 weeks. The results obtained were that after the intervention there was an increase in family independence and a decrease in patient blood sugar. Thus, it can be concluded that walking exercise is effective in increasing family independence in caring for and lowering blood sugar levels in DM patients